Sistem Pakar Batik Yogyakarta Berbasis Web - Gustin Sari Margiani Rahayu; Surjono; Wahyuni (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
Batik is an Indonesian traditional fabric dyeing method using wax to create patterns and designs. Batik is both an art and a craft, which is becoming more popular and well known in the world as a wonderfully creative medium. The designs and patterns of Indonesian batik are known to be very detailed, complicated, beautiful, and commonly used as a dress code for some special events. Given that the memory has its limitations and experts who understand batik is very limited, it is necessary to create an artificial expert in order to keep one of this cultural heritages can survive. The aim of this research is to develop and implement rule based expert system that can quickly and correctly identify the design and pattern of batik, especially batik from Yogyakarta. The system wull construct inferences from several type of inputs feeding to system, concerning the physical characteristic of the batik, such as colour of the background, colour of the design, styles, ornaments and fillers. The system will analyze the inputs using if-then algorithm in order to come to the conclusions. Implementing PHP as a programming language combined with MySQL as database tools, this batik expert systems can be developed and access via internet.